EVALUATION OF MODIFIED ALVARADO, RIPASA AND LINTULA SCORING SYSTEM AS DIAGNOSTIC TOOLS FOR ACUTE APPENDICITIS - Khan, Sana; Usama, Muhammad; Basir, Yasir; Muhammad, Saad; Jawad, Muhammad; Khan, Tooba; Usman, Ahmed; Abbas, Asim (Journal of Ayub Medical College Abbottabad, 2020)
Background: Commonest surgical emergency presenting to emergency departments with abdominal pain is acute appendicitis. Thus, to enable quick and accurate diagnosis of the condition various scoring systems have been developed. Among these, Alvarado and its modified version (Modified Alvarado) are the commonest. Whereas Raja Isteri Pengiran Anak Saleha Appendicitis (RIPASA) score showed promising results in Asian population. Similarly, Lintula score, which was initially developed for paediatric population, has now been validated for elderly too. This study is aimed to compare these in our regional population. Method: Project included consecutive 125 clinically suspected acute appendicitis patients. All were scored using Modified Alvarado, RIPASA and Lintula systems. Final diagnosis was based on histopathologic evaluation of excised specimen. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and diagnostic accuracy were computed for all these systems by using SPSS statistical software and ROC curves were plotted. Results: With cut-off of 7, Modified Alvarado was 62% specific, 83% sensitive and 65% accurate. While PPV and NPV were 94% and 33%, respectively. Whereas RIPASA yielded better results, i.e. sensitivity of 98.4%, specificity of 87%, PPV of 97%, NPV of 77% and diagnostic accuracy of 92%. Whereas Lintula showed sensitivity of 71%, specificity of 87%, PPV of 96%, NPV of 40 and accuracy of 73%. Conclusion: RIPASA demonstrated higher sensitivity, PPV, NPV and diagnostic accuracy than Modified Alvarado and Lintula scores. Hence this study approves use of RIPASA score in the region. However further research on the subject is required to back this inference. Keywords: Acute appendicitis; Modified Alvarado score; RIPASA score; Lintula score